Bacillus spp. Inhibit Edwardsiella tarda Quorum-Sensing and Fish Infection - Rafaela A. Santos (MDPI AG, 2021)
The disruption of pathogen communication or quorum-sensing (QS) via quorum-quenching (QQ) molecules has been proposed as a promising strategy to fight bacterial infections. Bacillus spp. have recognizable biotechnology applications, namely as probiotic health-promoting agents or as a source of natural antimicrobial molecules, including QQ molecules. This study characterized the QQ potential of 200 Bacillus spp., isolated from the gut of different aquaculture fish species, to suppress fish pathogens QS. Approximately 12% of the tested Bacillus spp. fish isolates (FI). were able to interfere with synthetic QS molecules. Ten isolates were further selected as producers of extracellular QQ-molecules and their QQ capacity was evaluated against the QS of important aquaculture bacterial pathogens, namely Aeromonas spp., Vibrio spp., Photobacterium damselae, Edwardsiela tarda, and Shigella sonnei. The results revealed that A. veronii and E. tarda produce QS molecules that are detectable by the Chr. violaceum biosensor, and which were degraded when exposed to the extracellular extracts of three FI isolates. Moreover, the same isolates, identified as B. subtilis, B. vezelensis, and B. pumilus, significantly reduced the pathogenicity of E. tarda in zebrafish larvae, increasing its survival by 50%. Taken together, these results identified three Bacillus spp. capable of extracellularly quenching aquaculture pathogen communication, and thus become a promising source of bioactive molecules for use in the biocontrol of aquaculture bacterial diseases.